PENGEMBANGAN TABLET EFERVESEN KOMBINASI BROKOLI DAN PEGAGAN DENGAN KOMBINASI ASAM DAN BASA - Yuliana Kusumawati; Erni Rustiani; Almasyuhuri Almasyuhuri (Faculty of Pharmacy, Universitas Muslim Indonesia, 2017)
Brocoli and pegagan is a plant that is easy to get and efficacious as antidemensia. The objective of this study was to formulate the plant into an effervescent tablet preparation and to determine the best formula with acid concentration variation. Dry extract of brocoli and pegagan is made by the method of escape then dried with vacuum dryer. The preparation is made by wet granulation method of 3 formula with weight of 4 gram per tablet. The granule test includes moisture content. Result of granule water content ˂5%. Granules are printed in special chambers and conditions and tested for quality. The result of uniform weight test of all formula meets the requirements of Pharmacopoeia Indonesia III; Hardness of tablets 12.06-12.52 kP; Friability of tablets 0.083-0.74%; Test of dissolution time of efervesen tablet ˂ 5 minutes. Preferred test results showed formula III with citric acid concentration: 1: 2 tartaric acid most preferred; Test result of asiatikosida content of pegagan extract is 0.08% and efervesen 0.005% tablet; Test results for vitamin C content of broccoli extract 13.859% and efevesen tablet 16.995%. The results of the physical quality test of effervescent tablets showed that the three formulas met the specified requirements. Stability test results for 8 weeks showed that the effervesen tablet of formula 3 met the requirements of physical quality during storage.